THE EFFECT OF PRODUCT QUALITY AND ADVERTISEMENTS ON PURCHASE DECISION OF TEH PUCUK HARUM IN SURABAYA - Sarwono, Abyansyah Hayyu; Pudjoprastyono, Hery (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
With the progression of time, the food and beverage industry has seen a rise in competition, prompting companies to implement various strategies to attract consumer interest and drive purchase decisions. Enhancing product quality and creating engaging advertisements are key strategies to influence consumer behavior. This study aims to investigate the impact of Product Quality and Advertising on Purchase Decisions, specifically focusing on Teh Pucuk Harum products in Surabaya. Employing a quantitative approach, the research targets individuals who have consumed Teh Pucuk Harum, are residents of Surabaya, and are at least 17 years old. The sample comprises 108 respondents from Surabaya. All tests performed using SmartPLS software met the reliability criteria. The study uses a quantitative research design with data analysis involving descriptive statistics and PLS analysis. The findings reveal that both Product Quality and Advertising significantly affect Purchase Decisions for Teh Pucuk Harum in Surabaya